Post‐discharge thrombosis and bleeding in medical patients: A novel risk score derived from ubiquitous biomarkers. Issue 5 (7th July 2021) - Woller, Scott C.; Stevens, Scott M.; Fazili, Masarret; Lloyd, James F.; Wilson, Emily L.; Snow, Gregory L.; Bledsoe, Joseph R.; Horne, Benjamin D.
Abstract: Background: Some hospitalized medical patients experience venous thromboembolism (VTE) following discharge. Prophylaxis extended beyond hospital discharge (extended duration thromboprophylaxis [EDT]) may reduce this risk. However, EDT is costly and can cause bleeding, so selecting appropriate patients is essential. We formerly reported the performance of a mortality risk prediction score (Intermountain Risk Score [IMRS]) that was minimally predictive of 90‐day hospital‐associated venous thromboembolism (HA‐VTE) and major bleeding (HA‐MB). We used the components of the IMRS to calculate de novo risk scores to predict 90‐day HA‐VTE (HA‐VTE IMRS) and major bleeding (HA‐MB IMRS). Methods: From 45 669 medical patients we randomly assigned 30 445 to derive the HA‐VTE IMRS and the HA‐MB IMRS. Backward stepwise regression and bootstrapping identified predictor covariates from the blood count and basic chemistry. These candidate variables were split into quintiles, and the referent quintile was that with the lowest event rate for HA‐VTE and HA‐MB; respectively. A clinically relevant rate of HA‐VTE and HA‐MB was used to inform outcome rates. Performance was assessed in the derivation set of 15 224 patients. Results: The HA‐VTE IMRS and HA‐MB IMRS area under the receiver operating curve (AUC) in the derivation set were 0.646, and 0.691, respectively. In the validation set, the HA‐VTE IMRS and HA‐MB IMRS AUCs were 0.60 and 0.643. Conclusions: Risk scores derived from components of routine labs ubiquitous in clinical care identify patients that are at risk for 90‐day postdischarge HA‐VTE and major bleeding. This may identify a subset of patients with high HA‐VTE risk and low HA‐MB risk who may benefit from EDT.